2001
DOI: 10.1006/bbrc.2001.4337
|View full text |Cite
|
Sign up to set email alerts
|

Associates with a Neurite-Outgrowth-Related Protein, SFAP75

Abstract: FIG. 2.Time course of Na ϩ -dependent Ca 2ϩ uptake in VC and NO. Na ϩ -dependent Ca 2ϩ uptake of both VC (s) and NO (OE) was determined by subtracting the values obtained in Na ϩ -containing buffer from the Na ϩ -free choline buffer. Each point represents the mean value Ϯ SEM (n ϭ 6). Two-way-ANOVA showed a significant difference of Ca 2ϩ uptake with time (P Ͻ 0.05) and Ca 2ϩ uptake of NO was significantly different when compared to VC (P Ͻ 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, we found the F‐actin crosslinking neurabin I and the cytosolic norbin as induced genes. In dendrites, neurabin employs its PDZ‐domain to interact with p70(S6k) and recruits protein phosphatase 1 isoforms to synapses (Burnett et al ., 1998; Terry‐Lorenzo et al ., 2002) while norbin colocalizes with the cytoplasmic tail of semaphorin 4C (Ohoka et al ., 2001). Thus, their up‐regulation 3 weeks after axotomy could indicate a plastic subicular response, involving alterations in membrane protein composition via PDZ‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found the F‐actin crosslinking neurabin I and the cytosolic norbin as induced genes. In dendrites, neurabin employs its PDZ‐domain to interact with p70(S6k) and recruits protein phosphatase 1 isoforms to synapses (Burnett et al ., 1998; Terry‐Lorenzo et al ., 2002) while norbin colocalizes with the cytoplasmic tail of semaphorin 4C (Ohoka et al ., 2001). Thus, their up‐regulation 3 weeks after axotomy could indicate a plastic subicular response, involving alterations in membrane protein composition via PDZ‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Norbin was found to interact with several membrane proteins enriched in the brain, including Sema4C, 13 several G-protein coupled receptors (GPCRs) from the family A such as the melanin-concentrating hormone receptor 1 (MCHR1) 14,15 and from Until recently and despite the studies of the physical proteinprotein interactions with Norbin, the functional and physiological consequences of interactions involving Norbin remained obscured. It has been reported that Norbin expression increases the steady-state cell surface level of MCHR1 and mGluR5, 2,14 suggesting that Norbin plays a key role in the trafficking of transmembrane proteins.…”
Section: Norbin Interacts With Membrane Proteins and Binds Phospholipidsmentioning
confidence: 99%
“…2 Truncation and mutagenesis studies indicate that the interactions between Norbin and membrane proteins involve the C-terminal part of Norbin and the membrane-proximal region of the membrane proteins. 2,13,14 However, the structural basis of these interactions is not understood. Recently, two sites responsible for Norbin binding were mapped on mGluR5.…”
Section: Involvement Of Norbin In Cell Signaling and Neuronal Functionmentioning
confidence: 99%
“…The in vivo function of ncdn is unknown. Ncdn was reported to bind in vitro to the cytoplasmic tail of Sema4c, a transmembrane semaphorin involved in axon guidance and synapse formation (Ohoka et al 2001). Recently a new binding partner of Ncdn was detected-phosphatidic acid, a product of phospholipase D which is involved in the propagation of the MAPK signalling cascade (Ktistakis et al 2003).…”
mentioning
confidence: 99%